Freedom in learning from family education perspective in covid 19 pandemic - Fatmi Fauzani Duski; Firman Firman; Rusdinal Rusdinal (International Journal of Technology, Innovation and Humanities, 2020)
In the era of pandemic covid 19, families become the most important tool in developing children's creativity. With the concept of "free learning" that became a stutter for the Minister of Education and Culture of the Republic of Indonesia, which can make students free in developing creativity. In this article will be described about freedom of learning in the era of pandemic covid 19 with a family perspective. This research is library research, which is basically qualitative research by analyzing how to instill family education in the concept of free learning during the covid 19 pandemic by means of distance learning (PJJ) which is currently an alternative to the running of the learning process and in meeting the demands of the curriculum in order to be achieved well